Molecular docking studies and in-vitro cholinesterase inhibitory activities of chemical constituents of Calophyllum gracilentum - Nurr Maria, Ulfa Seruji; Vivian Jong, Yi Mian; Thiruventhan, Karunakaran; Nor Hisam, Zamakshshari; Mah, Siau Hui; Natalie Vivien, Gunter; Mas Atikah, Lizazman; Arai, Masayoshi (Elsevier Ltd., 2024)
Calophyllum species are well known due to their abundance of potentially beneficial phytochemicals, such as xanthones, coumarins, and others. However, Calophyllum gracilentum is an understudied specie with very limited information. Medicinal plants have been proven to have therapeutic potential in managing neurological disorders associated with acetylcholinesterase (AChE) dysregulation. Still, there has been little investigation on Calophyllum plants for this purpose. Herein, we report on the isolation of a new oxygenated xanthone 5,10-dihydroxy-9-methoxy-2,2-dimethyl-12-(3-methylbut-2-enyl) pyrano[3,2-b] xanthen-6(2 H)-one (1) and eleven known xanthones (2–12), three chromanone acids (13–15), and phytosterols (16–18), respectively from the stem bark of the Calophyllum gracilentum. The evaluation of AChE inhibitory activity showed that all the extracts and xanthones (2, 5, 6, 8, 9, 12) tested have potential AChE inhibitory activity. Compounds (5) and (12) are prospective AChE inhibitors with IC50 values of 1.8 ± 0.0001 and 4.0 ± 0.0002 µmol/L. The molecular docking analysis demonstrated compound (5) and compound (12) bind well to the active site which is the anionic site containing Trp 84 and Asp 72 in the of Torpedo californica acetylcholinesterase (TcAChE) through π-π stacking, hydrogen bonding, and π-donor hydrogen bond from the xanthone ring, besides π-alkyl and π-σ interactions from the substituent group with the binding energy of − 11.1 kcal/mol for compound (5) and binding energy of − 10.4 kcal/mol for compound (12).